PSMA Theranostics: Current Status and Future Directions. (1st June 2018) - Rahbar, Kambiz; Afshar-Oromieh, Ali; Jadvar, Hossein; Ahmadzadehfar, Hojjat
Prostate-specific membrane antigen (PSMA) is a promising target for imaging diagnostics and targeted radionuclide therapy (theranostics) of prostate cancer and its metastases. There is increasing evidence of encouraging response rates and a low toxicity profile of radioligand therapy (RLT) of metastatic castration-resistant prostate cancer using 177 Lu-labeled PSMA ligands. In this article, we review the current status of diagnostics and therapy using radiolabeled PSMA ligands. We also suggest protocols for patient selection criteria and conduct of PSMA-based RLT. Challenges and opportunities of PSMA theranostics are discussed.